Microalgae: Bioactive Composition, Health Benefits, Safety and Prospects as Potential High-Value Ingredients for the Functional Food Industry - Josephine Ampofo; Lord Abbey (Foods, 2022)
Global population is estimated to reach about 9.22 billion by 2075. The increasing knowledge on the relationship between food biochemistry and positive health gives an indication of the urgency to exploit food resources that are not only sustainable but also impact human health beyond basic nutrition. A typical example of such novel food is microalgae, an aquatic microorganism with a plethora of diverse bioactive compounds including phenolics, carotenoids, vitamin B12 and peptides. Microalgal bioactive compounds have been shown to possess positive health effects such as antihypertensive, anti-obesity, antioxidative, anticancer and cardiovascular protection. Although, the utilization of microalgal biomass by the functional food industry has faced lots of challenges because of species diversity and variations in biomass and cultivation factors. Other documented challenges were ascribed to changes in functional structures during extraction and purification due to inefficient bio-processing techniques, inconclusive literature information on the bioavailability and safety of the microalgal bioactive compounds and the fishy odor and taste when applied in food formulations. In spite of these challenges, great opportunities exist to exploit their utilization for the development of functional foods. Microalgae are a renewable resource and have fast growth rate. Therefore, detailed research is needed to bridge these challenges to pave way for large-scale commercialization of microalgal-based healthy foods. The focus of this review is to discuss the potential of microalgae as natural ingredients for functional food development, factors limiting their acceptance and utilization in the food industry as well as their safety concerns with respect to human consumption.